Design and Implementation of the DuaEnam Garage Business In Sleman, Yogyakarta - Ivandeer Daffa Firstyansyah; Anas Hidayat (Cita konsultindo, 2024)
The establishment of the DuaEnam Garage business was due to support from the author's parents, who are also involved in the world of the vehicle business. This business follows the trend of vehicles that are currently busy in the market. DuaEnam Garage is located in Sleman Regency. Overall, this business prioritizes marketing through on line. This writing aims to find out whether digital marketing is feasible or not in the current era. In marketing through digital marketing, DuaEnam Garage also pays attention to good business ethics in digital marketing. With activities in paying attention to digital marketing strategies and business ethics, it can significantly influence the increase in visitors and better recognition of the DuaEnam Garage business as well as an increase in the number of followers and views on social media and the DuaEnam Garage marketplace.